Analysis of the Impact of Renewable Energy Development, Supporting Infrastructure, and Policy Support on the Sustainability of Rural Areas in Papua - Halomoan Hutajulu (Westscience Press, 2026)
This study aims to analyze the impact of renewable energy development, supporting infrastructure, and policy support on the sustainability of rural areas in Papua. A quantitative approach was applied using survey data collected from 140 respondents through structured questionnaires measured on a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate the measurement model and structural relationships among variables. The results indicate that renewable energy development and supporting infrastructure have a positive and significant influence on rural sustainability, highlighting the importance of energy access and infrastructure readiness in improving socio-economic and environmental conditions in rural communities. Supporting infrastructure emerges as the strongest predictor, suggesting that connectivity and operational support systems play a crucial role in ensuring long-term development outcomes. Meanwhile, policy support shows a positive but statistically insignificant effect, indicating that existing policies may require stronger implementation and alignment with local needs. The model demonstrates adequate validity, reliability, and predictive relevance, confirming its robustness in explaining sustainability outcomes. This study contributes to sustainable rural development literature by integrating technological, structural, and institutional perspectives, and provides practical implications for policymakers and stakeholders in designing more effective strategies to strengthen rural resilience and sustainability in Papua.